EXTRAPULMONARY TUBERCULOSIS SERVICES IN SIBERIA AND THE FAR EAST - E. V. Kulchavenya (Туберкулез и болезни лёгких)
Extrapulmonary tuberculosis is an "awkward" issue of public health: it can't be screened for, it is difficult to diagnose, bacteriological verification does not exceed 46% while the part of patients with isolated extrapulmonary lesions remains low among other cases of tuberculosis. The existing system of dispensary follow-up provides a significant impact on extrapulmonary tuberculosis incidence since according to its requirements, one (major) site of the disease is to be notified, which is usually respiratory tuberculosis. And specialists treating extrapulmonary tuberculosis are responsible for consulting of all tuberculosis patients relevant to their specialization.The objective of the study: to analyze the staff of specialists managing extrapulmonary tuberculosis patients in Siberia and the Far East.Subjects and methods. Special questionnaires filled in by specialists from TB dispensaries from Siberian and Far Eastern Federal Districts were analyzed; statistic reports (Form 8) from these Russian regions were studied.Results. In 2017, 550 people developed isolated extrapulmonary tuberculosis. Since 2008, bone and joint tuberculosis (40.7%) has been prevailing followed by urogenital tuberculosis (20.4%). 94 extrapulmonary tuberculosis specialists work in Siberian and Far Eastern Federal Districts, and 36.2% of them have been working for more than 30 years. Phthisioosteologists make 20.2% and urologists – 26.6%. Every forth specialist (28.7%) specializes in two fields, one of them is phthisiology.The excessive number of urologists can be explained by the changes in the epidemic situation: urogenital tuberculosis gave place to bone and joint tuberculosis. The existing health care system is rather inert and it could not change the profile of beds and train the relevant specialists in a prompt way.